The new work of writing across the curriculum : diversity and inclusion, collaborative partnerships, and faculty development - Perryman-Clark, Staci M. (Utah State University Press, 2023)
"A descriptive analysis of how institutions can and should work collaboratively to foster stronger intellectual activities around writing, particularly connected to campus-wide diversity, equity, and inclusion initiatives"--